2022
DOI: 10.1111/1750-3841.16126
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characteristics and in vitro digestibility of starches from colored quinoa (Chenopodium quinoa) varieties

Abstract: The quinoa flour processing is mostly subject to the properties of starch. Starches from four colored quinoa varieties, including white quinoa (QS‐W), yellow quinoa (QS‐Y), red (QS‐R), and black (QS‐B), were compared with respect to their physicochemical properties and in vitro digestibility. Results indicated that QS‐B exhibited the highest content of amylose (8.14%) (p < 0.05). All starch samples exhibited as irregular sphere with a particle size less than 3 µm. Results of the FT‐IR and X‐ray showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The diffraction patterns of starch in fermented dried noodles subjected to different drying conditions were similar, showing typical A‐type crystals with strong single diffraction peaks at 15° and 23°, weak diffraction peaks at 20° and connected double peaks at 17° and 18° (Fig. S2) (Peng et al ., 2022). This finding demonstrated that the drying conditions had a minor influence on the crystal type of starch in the fermented noodles.…”
Section: Resultsmentioning
confidence: 99%
“…The diffraction patterns of starch in fermented dried noodles subjected to different drying conditions were similar, showing typical A‐type crystals with strong single diffraction peaks at 15° and 23°, weak diffraction peaks at 20° and connected double peaks at 17° and 18° (Fig. S2) (Peng et al ., 2022). This finding demonstrated that the drying conditions had a minor influence on the crystal type of starch in the fermented noodles.…”
Section: Resultsmentioning
confidence: 99%
“…The higher D 50 , D [4, 3] , and D [3, 2] of the enzymatic method suggests that the presence of sodium bisulfite in the enzymatic method facilitated the procurement of large starch granules [ 28 ], and could not effectively purify starch granules, while the lower D 50 , D [4, 3] , and D [3, 2] of alkali and wet-milling methods indicated that sodium hydroxide present in the alkali method helped to penetrate water into starch followed by granule swelling and degraded amylose and amylopectin at the surface of the starch granules [ 29 , 30 ], whereas the wet-milling process also caused the loss of starch granules and ultimately changed the granule size distribution [ 9 ]. Moreover, Peng et al compared the physicochemical properties and in vitro digestibility of different quinoa varieties and observed that quinoa starch was damaged due to different starch isolating methods [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…This might have been because TBBF contains more dietary fiber and polyphenols, which reduced the digestibility of the TBDNs [ 16 ]. Noodles with an eGI below 55 are considered a low GI food [ 38 ]. Thus, all of the samples (TBBF-15, TBBF-25, and TBBF-35) meet this standard ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%